Chemical profiles of essential oils of two cultivars of Melaleuca cajuputi leaves and flowers - Le, Hong Thia; Huynh, Nguyen Tuong An (Journal of Phytology, 2024)
In the present study, the differences between the chemical compositions of the essential oils obtained from the leaves and flowers of two cultivars of M. cajuputi collected from Moc Hoa district, Long An province. By using Gas Chromatography-Mass Spectrometry, a total of 105 components have been identified in the essential oils of four samples of two M. cajuputi cultivars such as “Tràm gió” leaves, “Tràm gió” flowers, “Tràm cừ” leaves and “Tràm cừ” flowers. The Agglomerative Hierarchical Cluster (AHC) and Principal Component Analysis (PCA) were performed to show the similarities/dissimilarities in chemical compositions among the four studied samples. As a result, the components of the essential oils of four studied samples were divided into two clusters. Cluster I included two samples such as “Tràm gió” leaf and “Tràm gió” flower with high presence of 1,8-cineole (35.12 and 17.69%), linalool (3.31 and 5.03%), (R)-α-terpinyl acetate (9.17 and 8.1%). Cluster II comprised “Tràm cừ” leaf and “Tràm cừ” flower with the high concentration of α-pinene (9.87 and 12.19%), γ-terpinene (10.48 and 11.3%), p-mentha-2,4(8)-diene (8.8 and 12.7%).